The UN Zero Tolerance Policy’s Whereabouts: On the Discordance between Politics and Law on the Internal-External Divide - Machiko Kanetake (Amsterdam Law Forum, 2012)
Sex scandals involving UN peacekeepers have ignited media attention since the late 1990s. In order to reclaim its reputation, the UN has committed itself to the Zero Tolerance policy embodied in the Secretary-General’s Bulletin of 2003, which has been subject to detailed analysis. This paper’s aim is to reconsider the policy’s genesis and problems from the perspective of discordance between politics and law. I argue that the Zero Tolerance policy can be understood as the UN’s attempt to resolve discordance between political and legal lines which separate the UN (internality) from non-UN elements (externality). The political boundary internalises broader conduct and tasks within the UN. The legal boundary, however, externalises much of the conduct and tasks that are internalised by the political line. The place of the Zero Tolerance policy is therefore to substantially remedy such ‘discordance’ between politics and law, by aligning the policies of externalities with those of the UN.